2022
DOI: 10.1021/acsapm.1c01812
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Thermal Property Relationships of Polysilsesquioxanes for Thermal Insulation Materials

Abstract: For the development of polysilsesquioxanes (PSQs) as organic−inorganic hybrid materials for efficient thermal insulators, gaining a better understanding on the structure−thermal property relationship of PSQ gel films is essential. With this aim, PSQs were prepared via the sol−gel method to investigate the influence of residual alkoxy groups and substituents on the thermal insulation property of PSQ freestanding gel films. The thermal diffusivities of gel films prepared from polymethylsilsesquioxanes having eth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Indeed, M w linearly increased with the increase in the water/monomer molar ratio (Figure ), indicating that the molecular weight of PGPS could be controlled by varying the amount of water. This trend is consistent with the hydrolysis and polycondensation of bis­(triethoxysilyl)­ethane and triethoxymethylsilane by the nitrogen flow method. ,, …”
Section: Resultssupporting
confidence: 85%
See 3 more Smart Citations
“…Indeed, M w linearly increased with the increase in the water/monomer molar ratio (Figure ), indicating that the molecular weight of PGPS could be controlled by varying the amount of water. This trend is consistent with the hydrolysis and polycondensation of bis­(triethoxysilyl)­ethane and triethoxymethylsilane by the nitrogen flow method. ,, …”
Section: Resultssupporting
confidence: 85%
“…PGPS was synthesized by hydrolysis and polycondensation by the nitrogen flow method, as illustrated in Scheme . The nitrogen flow method is useful for controlling the molecular weight of PSQ by changing the water/monomer molar ratio, as reported in previous studies. ,, Therefore, PGPS samples were synthesized by changing the water/monomer molar ratio to obtain a polymer with different molecular weights, as illustrated in Table . With a water/monomer molar ratio of 1.2, the weight-average molecular weight ( M w ) and polydispersity index ( M w / M n ) of PGPS were 5200 and 2.0, respectively (entry 1 in Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To demonstrate the convenience of using MSQ-SiH to prepare the MSQ/TAIC hybrid films by hydrosilylation reaction, we prepared a PSQ film containing the isocyanurate ring by the polycondensation reaction of a polymethylsilsesquioxane having a molecular weight similar to that of MSQ-SiH (M w = 1200) and TESIC as a control experiment. First, we synthesized the polymethylsilsesquioxane by the sol−gel reaction of triethoxymethylsilane according to our previous paper 24 and TESIC by the hydrosilylation reaction of TAIC with triethoxysilane (Scheme 2). The 1 H NMR and HRMS of the as-prepared TESIC confirmed that it was obtained in high purity by simply removing the solvent from the reaction mixture under high vacuum.…”
Section: ■ Results and Discussionmentioning
confidence: 99%